2021
DOI: 10.1002/pri.1932
|View full text |Cite
|
Sign up to set email alerts
|

Building therapeutic alliances with patients in treatment for low back pain: A focus group study

Abstract: Background and Purpose Low back pain is a multidimensional disorder and a biopsychosocial management approach is recommended. However, recent data indicates that physiotherapists mainly focus on biomechanical aspects in treatment and struggle with addressing psychosocial barriers for recovery. We wanted to explore how physiotherapists express their experiences of building therapeutic alliances within a biopsychosocial perspective of low back pain. Methods Qualitative focus‐group interviews were performed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Twenty-two of the 75 included studies comprised qualitative research designs (12 patient perspective31 41–51; 5 physiotherapist perspective52–56; 5 mixed perspectives57–61), followed by quantitative designs (n=15) (longitudinal cohort studies n=11,22 62–71 secondary analysis of RCTs n=472–75), RCTs (n=15),76–90 systematic reviews (n=15),21 32 47 91–102 mixed methods (n=3),30 103 104 commentary (n=2),105 106 case reports (n=2)107 108 and narrative reviews (n=1) 109. See online supplement 4) for details of included studies and their quality appraisal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-two of the 75 included studies comprised qualitative research designs (12 patient perspective31 41–51; 5 physiotherapist perspective52–56; 5 mixed perspectives57–61), followed by quantitative designs (n=15) (longitudinal cohort studies n=11,22 62–71 secondary analysis of RCTs n=472–75), RCTs (n=15),76–90 systematic reviews (n=15),21 32 47 91–102 mixed methods (n=3),30 103 104 commentary (n=2),105 106 case reports (n=2)107 108 and narrative reviews (n=1) 109. See online supplement 4) for details of included studies and their quality appraisal.…”
Section: Resultsmentioning
confidence: 99%
“…We included the terms of mastery and self-efficacy under the umbrella term of confidence. There was evidence that the clinician’s confidence in managing LBP, and their perceived expertise and credibility, impacted the provision of information, reassurance and individualised prescription of exercise, which influenced the development and maintenance of positive therapeutic alliance 52 68 72 105. This was both in part due to patients perceiving greater attention from the clinicians, as well as the reinforcement of trust through patient’s perceptions of clinicians being highly credible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They came to the conclusion that more research is required to fully explore this issue, particularly from the perspective of therapists, in order to improve physical rehabilitation programs. In this light, Unsgaard-Tøndel and Søderstrøm [ 9 ] showed that PTs indicate four key elements for establishing a good therapeutic alliance with patients: (1) presence and empathy within a biopsychosocial perspective as central to building the therapeutic alliance; (2) active listening and the adaptation of the treatment to the specific patient; (3) clinical experience, which is important to integrate the psychological and social domains into physiotherapy management; and (4) the use of sensitive communications to assist patients in acquiring new insights about their possibilities. In the same direction, Brunner et al [ 10 ] found that PTs’ higher confidence in managing their patients was associated with higher patient-reported working alliances.…”
Section: Introductionmentioning
confidence: 99%